PERLINDUNGAN HUKUM TERHADAP INFORMASI PRIBADI TERKAIT PRIVACY RIGHT BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Ni Gusti Ayu Putu Nitayanti; Ni Made Ari Yuliartini Griadhi (Kertha Negara : Journal Ilmu Hukum, 2014)
This scientific work entitled Against Legal Protection of Personal InformationRelated Privacy Right based on Act Number 11 of 2008 about Information andElectronic Transactions an issue of concern that will be discussed in this paper. Thebackground of this scientific work with the development of internet users which causespersonal information Internet users increasingly vulnerable to cybercrime. Thisscientific work aims to understand the legal protection and legal sanctions for personalinformation related privacy right based on Act Number 11 of 2008 about Informationand Electronic Transactions. This scientific work using the normative by analyzing theproblem with the Act and the related literature. The conclusion of the writing of thisscientific work is owner's personal information protection of Act Number 11 of 2008about Information and Electronic Transactions in Article 30 and perpetrators of crimesagainst personal informationrelated privacy rightsmay be subject to civil sanctionsandcriminal sanctionsas stipulated in the Article 26 and Article 46 of Act Number 11 of2008 about Information and Electronic Transactions.